Terror flyers : the lynching of American airmen in Nazi Germany - Hall, Kevin T. (Indiana University Press, 2021)
"Terror Flyers examines the "lynch justice" (Lynchjustiz) committed against American airmen in Nazi Germany during World War II. Using engaging first-person accounts of downed pilots, as well as previously unused primary sources, Terror Flyers challenges the notion that such lynchings were exclusively the domain of Nazi party officials and soldiers. New evidence reveals ordinary German people executed Lynchjustiz as well. Initially occurring as a spontaneous reaction to the devastation of the Allied air campaign against the cities of the Third Reich, Lynchjustiz offered the Nazi regime a unique propaganda opportunity to harness the outrage of the German population. Fueled by inspiration from America's own history of the lynching of African Americans, Nazi propaganda exploited the very same imagery found in US publications to escalate the anger of the German people. Drawing heavily on the accounts of the downed airmen themselves, testimonies from the "flyer trials" held in Dachau during 1945-48, and rarely seen Nazi propaganda, Terror Flyers offers a new narrative of this previously overlooked aspect of the Allied campaign in Europe and suggests that at least 3,000 cases of lynch justice likely occurred between 1943 and 1946."--